2019
DOI: 10.3389/fendo.2019.00128
|View full text |Cite
|
Sign up to set email alerts
|

Additional Impact of Glucose Tolerance on Telomere Length in Persons With and Without Metabolic Syndrome in the Elderly Ukraine Population

Abstract: Rationale: Association between different components of metabolic syndrome and the rate of age-related telomere shortening was reported repeatedly, although some findings are inconsistent across studies, suggesting the need for further research on the topic. In the present study, we examined relationships between different components of metabolic syndrome (MetS); glucose tolerance reflected in 2-h post-load plasma glucose (2hPG) levels and age on the leukocyte telomere length (LTL) in Ukraine populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…An association of short LTL with higher risk for developing type 2 diabetes has been also demonstrated; this association, however, was significantly influenced by body mass index (BMI), diabetes type, age, region, and sex (Zhao et al, 2013 ; Willeit et al, 2014 ; Wang et al, 2016 ; Krasnienkov et al, 2018 ). Short LTL was also shown to be associated with different aspects of metabolic syndrome (Khalangot et al, 2017 , 2019 , 2020 ). Accelerated telomere shortening and low telomerase activity were shown to be associated with skeletal pathologies mediated by the age-related abnormal reconstruction of the subchondral bone, such as osteoporosis and osteoarthritis (Fragkiadaki et al, 2020 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…An association of short LTL with higher risk for developing type 2 diabetes has been also demonstrated; this association, however, was significantly influenced by body mass index (BMI), diabetes type, age, region, and sex (Zhao et al, 2013 ; Willeit et al, 2014 ; Wang et al, 2016 ; Krasnienkov et al, 2018 ). Short LTL was also shown to be associated with different aspects of metabolic syndrome (Khalangot et al, 2017 , 2019 , 2020 ). Accelerated telomere shortening and low telomerase activity were shown to be associated with skeletal pathologies mediated by the age-related abnormal reconstruction of the subchondral bone, such as osteoporosis and osteoarthritis (Fragkiadaki et al, 2020 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…The interactions between age, gender, and 2hPG levels were mostly non-linear, as shown by neural network modeling. 37 To our knowledge, such non-linearity of associations of LTL with age, glucose tolerance, and MetS has never been reported previously. Perhaps an increase in telomerase activity in individuals with the MetS subtype, which is characterized by a strong dyslipidemic profile along with the lack of hyperglycemia 40 could be the possible explanation for this phenomenon.…”
Section: Ltl In Patients With and Without Metabolic Syndromementioning
confidence: 67%
“…To address the question whether LTL is similarly associated with glucose levels in different hyperglycemic categories, we examined the correlations between LTLs and fasting and post-load glucose levels, and also several other metabolic characteristics in persons who did not receive glucose-lowering treatment in Ukraine. 3537 In our research conducted in randomly selected rural residents of Kyiv region, an increase in telomere length (according to LTL quartiles) was found to be associated with better glucose tolerance according to OGTT 2hPG data ( P = 0.03) and only with a tendency to decrease fasting plasma glucose (FPG) levels. 35 In different glycemic categories (normal, prediabetes, and T2D), LTL was inversely associated with glucose tolerance (according to 2hPG) in all categories, but with FPG in the T2D category only.…”
Section: Ltl In Different Hyperglycemic Conditionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Elderly MetS patients may increase risk of CVD from shorten telomere. A previous study found that MetS had a high risk of shorter telomere by three times (p 0.01) [18] which leads to atherosclerosis and CVD [19] . However, only three of the five diagnostic criteria for MetS were independent predictors for CVD in the elderly including SBP, FPG, and HDL-c ( Table 4 ).…”
Section: Discussionmentioning
confidence: 95%